CHF prediction in rod bundles using round tube data (Brazilian Journal of Radiation Sciences, 2021)
The present work concerns the use of 1995 CHF table for uniformly heated round tubes, developed jointly by Canadian and Russian researchers, for the prediction of critical heat flux in rod bundles geometries. Comparisons between measured and calculated critical heat fluxes indicate that this table can be applied to rod bundles provided that a suitable correction factor is employed. The tolerance limits associated with the departure from nucleate boiling ratio (DNBR) are evaluated by using statistical analysis.
Keywords: critical heat flux; subchannel code; CHF table